Linguistische Einheiten und ihre Varianz - Bzdęga, Andrzej Z. (Wydawnictwo Naukowe UAM, 1991)
The author establishes all kinds of segment units on the plane of constituents (infrastructure, size level) and representation (infrastructure) which are compatible with the taxonomic model of language and grammar as that of German. On the latter plane there occurs a differentiation of system units ("emic" according to Pike) and their variants (units of an allo or "etic" type) and the author pays particular attention to the proper identification of free (facultative) variants. The author keeps himself away from establishing variants resulting not from the representation of immediate constituents of units, but from the projection of indirect constituents. The notion of variation is finally extended onto the language as a whole, including in to it considerations on the subject of so called diacodes and language varieties.